Does Competition for Capital Discipline Governments? Decentralization, Globalization, and Public Policy - Cai, Hongbin; Treisman, Daniel (American Economic Review, 2005)
Does Competition for Capital Discipline Governments? Decentralization, Globalization, and Public Policy by Hongbin Cai and Daniel Treisman. Published in volume 95, issue 3, pages 817-830 of American Economic Review, June 2005